Knowledge Gaps in the Fetal to Neonatal Transition of Infants With a Congenital Diaphragmatic Hernia - DeKoninck, Philip L. J.; Horn-Oudshoorn, Emily J. J.; Knol, Ronny; Crossley, Kelly J.; Reiss, Irwin K. M. (Frontiers in Pediatrics, 2021)
Clinical research for infants born with a congenital diaphragmatic hernia (CDH) has until recently mainly focused on advances in prenatal and postnatal treatment. However, during the early perinatal transition period there are major physiological adaptations. For most infants these changes will happen uneventful, but for CDH infants this marks the beginning of serious respiratory complications. In recent years, there is emerging evidence that the clinical management during the perinatal stabilization period in the delivery room may influence postnatal outcomes. Herein, we discuss major knowledge gaps and novel concepts that aim to optimize fetal to neonatal transition for infants with CDH. One such novel and interesting approach is performing resuscitation with an intact umbilical cord, the efficacy of this procedure is currently being investigated in several clinical trials. Furthermore, close evaluation of neonatal physiological parameters in the first 24 hours of life might provide early clues concerning the severity of lung hypoplasia and the risk of adverse outcomes. We will provide an overview of trending concepts and discuss potential areas for future research.